Global Value Chain Reconfiguration and COVID-19: Investigating the Case for More Resilient Redistributed Models of Production. (February 2022) - Phillips, Wendy; Roehrich, Jens K.; Kapletia, Dharm; Alexander, Elizabeth
The COVID-19 pandemic shocked the global economy, laying bare the coordination challenges and vulnerabilities of global value chains (GVCs) across sectors. Governments, consumers, and firms alike have called for greater GVC resilience to ensure critical products are delivered to the right place, at the right time, and in the right condition. This article investigates whether GVC reconfiguration through the adoption of redistributed manufacturing (RDM) in local production can deliver greater resilience against unexpected, disruptive global events. It proposes actionable steps for managers to ensure more resilient GVCs in the face of global shocks.